2019
DOI: 10.1111/rode.12592
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well‐being and political participation: Empirical evidence from Ghana

Abstract: A large, extant literature examines the effect of political factors on individual subjective well‐being. These studies have treated political factors as a cause and subjective well‐being as an effect. A sparse but growing literature now advances the argument that subjective well‐being is a cause and voting or political participation an effect. In this paper we examine whether subjective well‐being influences voting and political participation in Ghana. Using data from Wave 6 of the World Values Survey in Ghana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Therefore, if an individual experiences a high level of subjective well-being, his or her protest intention and behavior are likely to decrease. This relational pattern has been observed in electoral processes when analyzing reasons for voting against an incumbent ruler and participating in protests (Ward 2019;Sulemana and Agyapong 2019). When voters report lower subjective well-being, their electoral decision is against the ruling party candidate (Ward et al 2021;Bravo 2016).…”
Section: Subjective Well-being and Political Participationmentioning
confidence: 83%
See 2 more Smart Citations
“…Therefore, if an individual experiences a high level of subjective well-being, his or her protest intention and behavior are likely to decrease. This relational pattern has been observed in electoral processes when analyzing reasons for voting against an incumbent ruler and participating in protests (Ward 2019;Sulemana and Agyapong 2019). When voters report lower subjective well-being, their electoral decision is against the ruling party candidate (Ward et al 2021;Bravo 2016).…”
Section: Subjective Well-being and Political Participationmentioning
confidence: 83%
“…Thus, it is expected that subjective well-being, which is linked to positive emotional experiences, would decrease the intentions to protest. However, other studies have not found that subjective well-being impacts political participation, such as voting or protesting (Sulemana and Agyapong 2019;Pirralha 2017;Pirralha 2018). In this context, subjective well-being could take on different explanatory roles, such as a moderating effect, which still requires further evaluation.…”
Section: Subjective Well-being and Political Participationmentioning
confidence: 92%
See 1 more Smart Citation
“…At present, research on political participation and the life satisfaction of urban residents is increasing, especially in Europe and America, but the extent such empirical survey exists in developing democratic countries is unknown [ 8 ]. Therefore, this study uses Chinese urban residents as the research object and uses specific income, education, and political status—variables to measure economic and social status—to investigate the influence mechanism of political participation on urban residents’ life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…In the perspective of political psychology, many studies have explored the importance of PP (Flavin & Keane, 2012;de Zuniga, Diehl, & Ardevol-Abreu, 2017) and also POTP (Galston, 2001;Strabac & Allberg, 2011;Johann, 2012;Coffe, 2013;Dejaeghere & van Erkel, 2017) for democratic countries, where these two variables are significant aspects to form robust and healthy democracy. In the psychological description, these two behaviors will emerge due to internal factors, such as cognitive capacity (Aars & Christensen, 2020), emotion (Valentino et al, 2011), psychological well-being (Sulemana & Agyapong, 2019), personality (Pruysers, Blais, & Chen, 2019) and other internal psychological factors. However, in order to generate robust democracy, people should have awareness not just for ordinary participation but should be Voluntary Participation (VP).…”
Section: Introductionmentioning
confidence: 99%